Expression genome-wide association study identifies that phosphatidylinositol-derived signalling regulates ALUMINIUM SENSITIVE3 expression under aluminium stress in the shoots of Arabidopsis thaliana. (January 2021) - Sadhukhan, Ayan; Agrahari, Raj Kishan; Wu, Liujie; Watanabe, Toshihiro; Nakano, Yuki; Panda, Sanjib Kumar; Koyama, Hiroyuki; Kobayashi, Yuriko
Highlights: Expression GWAS of ALS3 in the shoots of Arabidopsis under aluminium stress. Mutants of PLC9, CDPK32 and ANAC071 suppressed ALS3 in the shoots. Phospholipase C signaling is upstream signal of ALS3 expression. Abstract: To identify unknown regulatory mechanisms leading to aluminium (Al)-induction of the Al tolerance gene ALS3, we conducted an expression genome-wide association study (eGWAS) for ALS3 in the shoots of 95 Arabidopsis thaliana accessions in the presence of Al. The eGWAS was conducted using a mixed linear model with 145, 940 genome-wide single nucleotide polymorphisms (SNPs) and the association results were validated using reverse genetics. We found that many SNPs from the eGWAS were associated with genes related to phosphatidylinositol metabolism as well as stress signal transduction, including Ca 2+ signals, inter-connected in a co-expression network. Of these, PLC9, CDPK32, ANAC071, DIR1, and a hypothetical protein (AT4G10470) possessed amino acid sequence/ gene expression level polymorphisms that were significantly associated with ALS3 expression level variation. Furthermore, T-DNA insertion mutants of PLC9, CDPK32, and ANAC071 suppressed shoot ALS3 expression in the presence of Al. This study clarified the regulatory mechanisms of ALS3 expression in the shoot and provided genetic evidence of the involvement of phosphatidylinositol-derived signal transduction under Al stress.